Ketidaklancaran Membaca pada Siswa Sekolah Dasar faktor penyebab dan upaya penangannya: Studi Kasus Siswa Kelas IV SD Negeri 09 Kayu Aro - Lusi Nurlaili; Ari Suriani (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This research aims to identify the causes and efforts to address Reading Fluency Issues among Elementary School Students: Case Study of Fourth Grade Students at SD Negeri 09 Kayu Aro. This study conducts a descriptive qualitative research with a case study. Abid Aqila Pranaja, a 10-year-old fourth-grade student, is the subject of the study. Interviews with teachers and direct observations in the classroom are part of the data collection methods. The results of the survey and observations conducted in the fourth-grade elementary school class show that one student is experiencing reading difficulties. The types of reading difficulties experienced by the student include difficulty recognizing letters, difficulty reading words, difficulty distinguishing between vowels and consonants, difficulty blending letters and syllables into a single word, and lack of attention to punctuation while reading. The teacher identified several factors causing reading difficulties, namely two internal factors and external factors.